2005
DOI: 10.1021/es048300u
|View full text |Cite
|
Sign up to set email alerts
|

Simple Method for Quantifying Microbiologically Assisted Chloramine Decay in Drinking Water

Abstract: In a chloraminated drinking water distribution system, monochloramine decays due to chemical and microbiological reactions. For modeling and operational control purposes, it is necessary to know the relative contribution of each type of reaction, but there was no method to quantify these contributions separately. A simple method was developed to do so. It compares monochloramine decay rates of processed (0.2 microm filtered or microbiologically inhibited by adding 100 microg of silver/L as silver nitrate) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 10 publications
3
48
0
Order By: Relevance
“…Earlier findings (Sathasivan et al, 2005(Sathasivan et al, , 2008Bal Krishna et al, 2013) showed that the behavior (mild nitrification mediated by CDOs) under high chloramine residual is noticed until the onset of nitrification. Earlier findings (Sathasivan et al, 2005(Sathasivan et al, , 2008Bal Krishna et al, 2013) showed that the behavior (mild nitrification mediated by CDOs) under high chloramine residual is noticed until the onset of nitrification.…”
Section: Implications For Further Research and Practicementioning
confidence: 94%
“…Earlier findings (Sathasivan et al, 2005(Sathasivan et al, , 2008Bal Krishna et al, 2013) showed that the behavior (mild nitrification mediated by CDOs) under high chloramine residual is noticed until the onset of nitrification. Earlier findings (Sathasivan et al, 2005(Sathasivan et al, , 2008Bal Krishna et al, 2013) showed that the behavior (mild nitrification mediated by CDOs) under high chloramine residual is noticed until the onset of nitrification.…”
Section: Implications For Further Research and Practicementioning
confidence: 94%
“…Chemical decay of chloramine is described by a complex set of reactions in the US EPANET MSX and Innovyze H 2 OMap MSX software [27]. Chemical stability of chloramine is not a limiting factor because chloramine (as formed for water disinfection) decays by less than 5% per day [28]. Therefore, after 10 d, there would still be more than 50% of chloramine available.…”
Section: Determination Of Maximum Acceptable Doc In Treated Watermentioning
confidence: 99%
“…Nitrite is not typically found in tap water, but it can build up to significant concentrations in the distribution system because of nitrification (Kirmeyer et al, 1995). Some research indicates that the chloramines loss could be caused principally by nitrite when nitrification occurs (Sathasivan et al, 2005;Yang et al, 2008). Under water treatment conditions, it has been indicated that the direct nitrite oxidation of chloramines could result in the chloramines loss (Lieu and Roy, 1993;Margerum et al, 1994).…”
Section: Chloramines Bulk Decay In Collected Distribution Systemmentioning
confidence: 99%